Diagnostic tests toolkit - Thompson, Matthew J.; Van den Bruel, Ann.; Wiley InterScience (Online service) (Oxford : Wiley-Blackwell, 2012)
This new volume in the Toolkit series is designed for clinicians and junior researchers who need to interpret the evidence for the effectiveness of the many diagnostic tests now available. Exceptionally user-friendly, this pocket-sized textbook realizes readers are not experts in diagnostic test interpretation. The authors cover a variety of issues, from how to design diagnostic test studies to understanding the results of diagnostic tests and interpreting the findings for clinical practice and health care policy.
Front Matter -- Diagnosis in Evidence-Based Medicine -- Evaluating New Diagnostic Tests -- Asking an Answerable Clinical Question -- Finding the Evidence: How to get the most from your Searching -- Selecting Relevant Studies -- Sources of Bias in Diagnostic Studies -- Measures of Discrimination of Diagnostic Tests -- Using Diagnostic Information in Clinical Practice -- Screening Tests -- Systematic Reviews of Diagnostic Test Accuracy Studies -- Appendix 1: Evidence-Based Medicine b6 (BA Glossary of Terms -- Appendix 2: Further Reading -- Index -- STARD Checklist.s
Includes bibliographical references and index.
Print version record.
Keywords: Diagnosis -- Handbooks, manuals, etc; Function tests (Medicine) -- Handbooks, manuals, etc; MEDICAL -- Diagnosis; MEDICAL -- Laboratory Medicine; MEDICAL -- Nursing -- Assessment & Diagnosis; Diagnosis; Function tests (Medicine); Diagnostic Techniques and Procedures; Evidence-Based Medicine; Electronic books; Handbooks and manuals; Handbooks